The relationship between volatility, volume and open interest: Some evidence from the South African futures market - E. V.D.M. Smit; M. W. Louw (South African Journal of Business Management, 1996)
Using the methodology devised by Bessembinder Seguin, the relationships between volatility on the one hand and volume and market depth in the South African futures market are examined. Daily mark-to-market prices, trading volumes and open interest on six futures contracts traded on SAFEX over the period 1990 to 1994 are utilized. The evidence suggests that linking price volatility to total volume does not capture all information. When total volume is divided into expected and unexpected components, the latter is shown to have a more substantial effect on volatility. Furthermore, coefficients pertaining to open as well as unexpected open interest tend to be negative, implying that lower volatility shocks are associated with a given volume in deeper markets. It is further shown that positive unexpected volume shocks are associated with higher levels of volatility and that asymmetry exists, insofar as positive shocks have larger effects on volatility than negative shocks.
Keywords: 650